Mevalonate Metabolism Regulates Basal Breast Cancer Stem Cells and Is a Potential Therapeutic Target123. (18th June 2012) - Ginestier, Christophe; Monville, Florence; Wicinski, Julien; Cabaud, Olivier; Cervera, Nathalie; Josselin, Emmanuelle; Finetti, Pascal; Guille, Arnaud; Larderet, Gaelle; Viens, Patrice; Sebti, Said; Bertucci, François; et al.
Abstract: There is increasing evidence that breast tumors are organized in a hierarchy, with a subpopulation of tumorigenic cancer cells, the cancer stem cells (CSCs), which sustain tumor growth. The characterization of protein networks that govern CSC behavior is paramount to design new therapeutic strategies targeting this subpopulation of cells. We have sought to identify specific molecular pathways of CSCs isolated from 13 different breast cancer cell lines of luminal or basal/mesenchymal subtypes. We compared the gene expression profiling of cancer cells grown in adherent conditions to those of matched tumorsphere cultures. No specific pathway was identified to be commonly regulated in luminal tumorspheres, resulting from a minor CSC enrichment in tumorsphere passages from luminal cell lines. However, in basal/mesenchymal tumorspheres, the enzymes of the mevalonate metabolic pathway were overexpressed compared to those in cognate adherent cells. Inhibition of this pathway with hydroxy‐3‐methylglutaryl CoA reductase blockers resulted in a reduction of breast CSC independent of inhibition of cholesterol biosynthesis and of protein farnesylation. Further modulation of this metabolic pathway demonstrated that protein geranylgeranylation (GG) is critical to breast CSC maintenance. A small molecule inhibitor of the geranylgeranyl transferase I (GGTI) enzyme reduced the breast CSC subpopulation both in vitro and in primary breast cancer xenografts. We found that the GGTI effect on the CSC subpopulation is mediated by inactivation of Ras homolog family member A (RHOA) and increased accumulation of P27 kip1 in the nucleus. The identification of protein GG as a major contributor to CSC maintenance opens promising perspectives for CSC targeted therapy in basal breast cancer. STEM CELLS 2012;30:1327–1337